Chronological evaluation of the synthesis techniques of nanocrystalline Fe73.5Cu1Nb3Si13.5B9 soft magnetic alloy - Nur-E-Alam M.; Bhattacharjee A.; Paul D.P.; Hakim M.A.; Islam M.A.; Kiong T.S.; Amin N.; Faruque M.R.I.; Khandaker M.U. (Elsevier Ltd, 2024)
In this review article, we focus on the synthesis process and properties of Fe-Si-B-based soft magnetic alloys that exhibit superior magnetic properties. The process parameters related to the synthesis and characterization of these types of alloys are studied widely and investigated the properties observed in nanocrystalline Cu and Nb-dopped Fe-Si-B-based magnetic alloys. The properties of these materials are an exceptional combination of high permeability, high Curie temperature, low core losses and anisotropy energy, and near zero effective magnetostriction suitable for various applications such as magnetic field sensors, sensors for non-destructive evaluation of materials, motors, transformer cores, electric vehicles, etc. A significant number of research works have been conducted so far and more research is continued to improve their properties in various ways including engineering of materials composition, optimization of synthesis processes, and parameters for easy integration into modern devices. This review article aims to demonstrate a comparison study of the properties of Fe-Si-B- based soft magnetic alloys and to provide the latest updates on their developments toward tailoring the extrinsic (coercivity, and permeability) and intrinsic (Curie temperature and saturation magnetization) properties for conquering the subsequent area of applications. 2023 Elsevier Ltd